HOW TO EVALUAT EFFICIENCY OF THE EXPORT STRATEGIES (Globalization and Business, 2018)
The paper reviews the specific topics of the formulation and management of the Export Strategies. Export Strategies became of vital importance for Georgia. After the signing DCFTA with EU Georgian officials were wondering that the export potential of Georgia would be utilized in the best possible way. Unfortunately utilization of export potential is only possible by developing and executing Export STrategies.The author reviews different methods of evaluating the export potential on different markets.In addition to it the article reviews different indicators for evaluating the efficiency of the export strategies.